Penerapan Metode Simulasi Dalam Meningkatkan Hasil Belajar PKn Pada Murid Kelas IV SD Negeri Mangasa Kecamatan Somba Opu Kabupaten Gowa - Musdalifah Syahrir (JED (Jurnal Etika Demokrasi), 2018)
This research is a classroom action research that aims to improve the learning result of Civics by using Simulation method. The subject of this research is fourth grade students of SD Negeri Mangasa Kec. Somba Opu Kab. Gowa with 24 students consisting of male students as many as 15 people and 9 female students. Data collection through students activity observation sheets was analyzed qualitatively, and students' learning outcomes were analyzed quantitatively. The increase of student learning result quantitatively can be seen from the average of student learning outcomes in the first cycle is 62.91 with the percentage of learning completeness 45.83% increase in cycle II to 75.41 with the percentage of learning mastery reach 87.5%. While the average student learning outcomes before the holding of classroom action research is 59.37. Qualitatively, it can be seen from the student activity during the learning process from cycle I to cycle II has increased. This can be seen from the number of students who pay attention to the explanation of the teacher in cycle I 69.79% increased to 81.25 in cycle II, students who are active in discussions with the group about the role to be played in cycle I 68.75% increased to 81.25 % in cycle II, students who actively play a role in cycle I 64.58% increased to 87.5% in cycle II, students who pay attention to other groups in role play in cycle I 66.66% increased to 86.45% II, and students who concluded the subject matter in cycle I 12.5% increased to 20.83% in cycle II.Keywords: Simulation Method, Learning Outcomes, Student